A Model for Predicting Unsafe Induced Abortion among Women in India - Kumar, Anup; Kishun, Jai (Indian Journal of Community Health, 2020)
Background: Unsafe abortion is one of the major cause of maternal morbidity and mortality. Approximately 15.6 million abortions take place every year in India of which a significant proportion is unsafe. Objective: To explore risk factors associated with unsafe induced abortion. Method: National Family Health Survey-IV data have 82,369 women aged between 15-49 years who responded about their aborted /miscarriage/stillbirth is used. Out of these total women, 8,878 were induced aborted and found eligible. Result: Of the total induced aborted, 30.6% of women are unsafe induced abortion. Women age between 35-49 years are 53% more likely to have unsafe induced abortion than age between 15-19 years. Women living in rural areas have 26% less likely to unsafe abortion than women living in urban areas. Women who have knowledge about the fertile period are 35% less likely to have unsafe abortion than no correct knowledge. Unsafe induced abortion is found increasing as education and wealth index are increasing. Conclusion: Unsafe induced abortion is a large contributor to maternal morbidity and mortality. Awareness of contraceptives use, Medical Termination of Pregnancy (MTP) and Comprehensive Abortion Care (CAC) service should be increased through media exposure